2023
DOI: 10.1002/tox.23984
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of curcumin nanoparticles in rat liver fibrosis caused by thioacetamide

Aliaa M. Radwan,
Shahenda A. Fatoh,
Ahmed Massoud
et al.

Abstract: Although curcumin possesses anti‐inflammatory, antioxidant, and cytoprotective qualities, its low absorption limits its medicinal uses. Before examining how curcumin influenced rats' liver fibrosis when thioacetamide (TAA) was produced, the current study employed nanoparticles (NPs) to improve curcumin bioavailability. Sixty mature rats were separated into six groups (Group 1, control; Group 2, curcumin; Group 3, curcumin nanoparticles; Group 4, TAA; Group 5, TAA + curcumin; Group 6, TAA + curcumin NPs). TAA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Conversely, hepatocyte proliferation decreases upon treatment with hepatoprotective medications [27,28]. Our results corroborate those of previous studies that reported the downregulation of PCNA in the hepatocytes of rats injected with TAA after treatment with natural compounds [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, hepatocyte proliferation decreases upon treatment with hepatoprotective medications [27,28]. Our results corroborate those of previous studies that reported the downregulation of PCNA in the hepatocytes of rats injected with TAA after treatment with natural compounds [40,41].…”
Section: Discussionsupporting
confidence: 92%